ความสัมพันธ์ของทันตสุขศึกษากับการพบเชื้อราแคนดิดาในช่องปากของผู้ป่วยโรคไลเคนแพลนัสที่ได้รับการรักษาด้วยยาฟลูโอซิโนโลน อะเซทโทไนด์ ความเข้มข้นร้อยละ 0.1 - วรางคณา ยรรยงเกษมสุข (จุฬาลงกรณ์มหาวิทยาลัย, 2013)
Lichen planus is a chronic mucocutaneous disorder causing chronic inflammation of oral mucosa. At present, topical corticosteroids are widely used in order to reduce inflammation and discomfort of the patients. One of the undesirable side effects of topical steroids is the increased risk of oral candidiasis. Up to now, a number of researches showed that people who have been introduced to properly oral health care will result in reducing number of oral microbes. The aim of this research was to study the impact of oral hygiene instruction on the presence of Candida in oral lichen planus patients undergoing treatment with 0.1% fluocinolone acetonide. The presence of oral Candida was assessed by imprint culture, concentrated oral rinse technique including plaque index measurement before oral hygiene instruction, 1 month and 3 months later. The results showed the statistical difference of plaque index score between before and after oral hygiene instruction (P0.05). Despite the effective of oral hygiene instruction in reducing dental plaque, there has no effect on the presence of oral Candida in oral lichen planus patients treated with 0.1% Fluocinolone acetonide.